2017
DOI: 10.3847/1538-4357/aa9072
|View full text |Cite
|
Sign up to set email alerts
|

The Stellar Content of the Infalling Molecular Clump G286.21+0.17

Abstract: The early evolution during massive star cluster formation is still uncertain. Observing embedded clusters at their earliest stages of formation can provide insight into the spatial and temporal distribution of the stars and thus probe different star cluster formation models. We present near-infrared imaging of an 8 ×13 (5.4pc×8.7pc) region around the massive infalling clump G286.21+0.17 (also known as BYF73). The stellar content across the field is determined and photometry is derived in order to obtain stella… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 36 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…Such a mechanism could be consistent with a larger-scale cloud-cloud collision scenario that has been reported in other starforming regions (e.g., Furukawa et al 2009;Fukui et al 2014;Gong et al 2017). Andersen et al (2017) analysed the stellar population in G286 and found evidence for at least three different sub-clusters associated with the molecular clump based on differences in extinction and disk fractions. It is un-clear how the dense gas distribution and ongoing cluster formation might be related with these past star formation events.…”
Section: Core To Core Velocity Dispersionsupporting
confidence: 84%
“…Such a mechanism could be consistent with a larger-scale cloud-cloud collision scenario that has been reported in other starforming regions (e.g., Furukawa et al 2009;Fukui et al 2014;Gong et al 2017). Andersen et al (2017) analysed the stellar population in G286 and found evidence for at least three different sub-clusters associated with the molecular clump based on differences in extinction and disk fractions. It is un-clear how the dense gas distribution and ongoing cluster formation might be related with these past star formation events.…”
Section: Core To Core Velocity Dispersionsupporting
confidence: 84%
“…G286.21+0.17 (hereafter G286) is a massive protocluster associated with the η Car giant molecular cloud at a distance of 2.5 ± 0.3 kpc, in the Carina spiral arm (e.g., Barnes et al 2010, hereafter B10;Andersen et al 2017). G286 has been claimed to be ∼ 10 4 M (B10), which would make it the most massive and densest of the 300 HCO + (1-0) clumps studied by Barnes et al (2011) and Ma et al (2013), but an assessment of its dust mass from Herschel imaging data suggests a lower mass of ∼ 2000 M (Ma et al, in prep.).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous studies, G286 clump is on the edge of HII region A (see B10). Both G286 and HII region A are found to be near HII region B (Gum31), which is at the same distance (d∼2.5 kpc) and is excited by a young stellar cluster NGC3324 (Cappa et al 2008;Barnes et al 2010;Ohlendorf et al 2013;Andersen et al 2017). HII region B is strongly interacting with the surrounding interstellar medium, and it may likely also affect the evolution of G286 and HII region A.…”
Section: Continuum Emissionmentioning
confidence: 99%
“…This work is focused on the dense clump. Andersen et al (2017) suggests the cluster are very young with a rich population of pre-main-sequence stars with a disk fraction ranging from 27% to 44% for a magnitude and extinction limited sample. Cheng et al (2020b) presents a near-infrared (NIR) variability analysis toward the G286 protocluster, suggesting it as being an extreme case of an outburst event that is still ongoing.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation